2015
DOI: 10.12775/oec.2015.017
|View full text |Cite
|
Sign up to set email alerts
|

Support for renewable energy in Germany as an example of effective public policy

Abstract: This article aims to analyze the process of energy transformation in Germany and renewable energy state support as an example of a strategic and effective policy. Energy transition in Germany, which leads to replacement of conventional energy with renewable sources and increase of energy efficiency is a long-term project requiring a strong state intervention. This project is supported with European Union green energy policy giving favorable legal and institutional framework for green technologies development. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 2 publications
0
5
0
1
Order By: Relevance
“…The one group of scientists proved that the main goal of green investment is declining of CO 2 emission [32][33][34][35][36][37][38][39][40][41][42][43][44][45]. The third group of scientists defined green investment as investment into renewable energy [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. In this case, it is necessary to investigate and develop the universal approach to define and classify green investment which will be based on the classification of green assets.…”
mentioning
confidence: 99%
“…The one group of scientists proved that the main goal of green investment is declining of CO 2 emission [32][33][34][35][36][37][38][39][40][41][42][43][44][45]. The third group of scientists defined green investment as investment into renewable energy [46][47][48][49][50][51][52][53][54][55][56][57][58][59][60][61][62][63]. In this case, it is necessary to investigate and develop the universal approach to define and classify green investment which will be based on the classification of green assets.…”
mentioning
confidence: 99%
“…Por ello, se ha identi cado que hacer inventarios de disponibilidad regional de recursos para energías no convencionales es vital para lograr resultados que eviten mayores desigualdades entre regiones (Bruckman et al, 2018), para lo cual la política pública es un instrumento necesario. Sin embargo, el rol de la política, en aras de la transición energética, se destaca en el campo de la regulación en tanto debe generar su cientes estímulos que hagan atractivo el sector (Baran, 2015;Philp, 2015) como "castigos" en términos de tributación o excedentes de pago a los sectores que se apoyan en combustibles fósiles (Monasterolo y Raberto, 2019).…”
Section: Transición Energéticaunclassified
“…There are imbalances in the countries included in the samples of previous research. The Asia descriptor has 6446 appearances in the 40 years, with China in 76 cases, followed by Turkey in 48 cases, Taiwan (25), Malaysia (20), and Pakistan (15). These are the countries with the highest frequency of occurrences; the other countries record less than 20 occurrences in total cases, except Tunisia (25).…”
Section: Frequency Of Descriptor Occurrencesmentioning
confidence: 99%
“…The analysis further demonstrated that energy is one of the determinant vectors that influence economic growth, especially gross domestic product [10][11][12][13]. At the same time, the reciprocal is true, in the sense that economic development (characterized mainly by increase of GDP per capita) leads to an increase in energy demand (implicitly, energy production) and a diversification of its sources [14], triggering effective public policies [15,16].…”
Section: Introductionmentioning
confidence: 99%